Local banking and local economic growth in Italy: Some panel evidence - Guglielmo Maria Caporale; Stefano Di Colli; Roberto Di Salvo; Juan Sergio Lopez (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper provides new evidence on the contribution of local banking to local economic growth (i.e. at county level - the Italian "province") in Italy. A comprehensive dataset is used, which includes control variables for social capital and human capital as well as indicators of the quality of local infrastructures and the production structure of the local economy. A linear within-estimator technique with fixed effects is applied to a modified version of the so-called Barro regression (Cecchetti and Karrhoubi, 2013) in order to address the well-known econometric issues of reverse causality and estimation bias resulting from unobserved district-specific influences.
Keywords: C33; E44; G01; G32; 330; bank lending; local growth; panel data